Can an exotic tree (Jackfruit, Artocarpus heterophyllus Lam.) influence the non-volant small mammals assemblage in a protected area of Atlantic Forest?. (26th September 2020) - Gama-Matos, Rayanne; Ferreguetti, Átilla Colombo; Mekiassen do Nascimento, Giulia; Pereira-Ribeiro, Juliane; Vagmaker, Natália; Júnior Boazi, Alex; Dantas Isidoro Grisóstomo, Walker; Rocha, Carlos Frederico Duarte; Bergallo, Helena Godoy
Abstract: Jackfruit ( Artocarpus heterophyllus Lam.) is an exotic invasive plant species in the Brazilian Atlantic Forest that causes changes in the environment through the release of allelopathic substances and has high fruit production. We aimed to understand the potential effects of the jackfruit on the non-volant small mammal assemblage in an area protected by law, in the municipality of Cariacica – Espírito Santo, south-eastern Brazil. We sampled the small mammals assemblage using live traps in 18 sites, eight with jackfruit and 10 without. We ordinated the assemblage and tested possible differences in species richness and abundance according to the jackfruit density. We recorded 31 species of non-volant small mammals, with 13 species endemic to the Atlantic Forest. Jackfruit species can affect both positively and negatively the studied assemblage of non-volant small mammals. For species with a frugivory habit, jackfruit has a positive effect favouring these species. On the other hand, for insectivorous species, jackfruit represents an impact inhibiting the presence of these species in an area with high jackfruit density. The results presented are the first step in understanding the effect of this invasive species on a small mammals assemblage and initiating a monitoring of these species in areas affected by jackfruits. Furthermore, management of jackfruits in this protected area is required.